INTERCONNECTIVITY: DATA NETWORK PLANNING, ONE OF THE BASES OF INDUSTRY 4.0 (International Seven Journal of Multidisciplinary, 2025)
The German government proposes a new industrial era like Industry 4.0. Hyperconnectivity is a defining characteristic of the new era. The current and future technological advances should allow the creation of a convergent network that meets all the information needs of Industry 4.0. Convergent networks or multi-service networks refer to the integration of digital voice, data and video services through communication networks in a single network based on IP (Internet Protocol) as a network level protocol. This article presents a project methodology for network structures for interconnectivity in Industry 4.0.